Selective epicardial pulsed field ablation of atrial ganglionated plexi causes anti-arrhythmic prolongation of refractoriness: demonstration of feasibility in cardiac surgery patients. (19th May 2022) - De Groot, JR; Shaburishvili, T; Skalsky, I; Van Zyl, M; O Brien, B; Reilly, J; Coffey, K; Neuzil, P; Reddy, VY
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): EU Horizon 2020 SME Instrument. Background: Epicardial ganglionated plexi (GP) play a significant role in the initiation and maintenance of atrial fibrillation. However, modulation of this effect, through GP ablation, has had limited success; outcomes being confounded by unnecessary atrial tissue ablation and inability to access and ablate all of the atrial GPs. Selective pulsed field ablation (PFA) of GPs, using epicardial access, provides the opportunity to better identify the role of GP ablation in the treatment of atrial fibrillation. Purpose: This study aimed to assess the safety and feasibility of selective GP ablation in patients undergoing elective coronary artery bypass grafting (CABG). It was hypothesized that GP ablation would provide an acute extension of atrial tissue refractoriness, which constitutes its antiarrhythmic effect. Methods: Using a monopolar, monophasic PFA system, atrial GPs were ablated in nineteen patients with or without atrial fibrillation, undergoing CABG. The Oblique Sinus GP, Right Superior GP, Transverse Sinus GP, Left Superior GP and Ligament of Marshall GP were each ablated with up to sixty PFA pulses of 1000 V amplitude and 100 µs pulse width. Atrial Effective Refractory Period (AERP) was measured before and after all GP ablations, at the left atrial appendage (LAA) and on the right atrium (RA). Patients were monitored through to discharge for post-operative atrial fibrillation (POAF). Results: Complete ablation of the GPs was performed in nineteen patients (aged 63.4 ± 6.6 years, 63.1% male) immediately after sternotomy. Electric field pulses were ECG-gated, with energy delivery during the ventricular refractory period. All GP sites were successfully accessed and ablated; all patients progressed immediately to their planned elective surgery and were discharged on schedule. Procedure time, for all GP ablations and AERP measurements was in the range 35-45 minutes. Thirteen valid pre- and post-ablation datasets were obtained. AERP (LAA and RA combined) increased upon GP ablation on average by 23% (220 ± 46 ms pre-ablation versus 269 ± 59 ms post-ablation, p = 0.002). Four patients experienced POAF; there was no evident correlation between POAF and AERP data. Only three of the enrolled patients had a prior history of AF; none of these exhibited AF on 24-hour Holter monitoring at 3-month follow-up. Conclusions: Selective epicardial PFA of GPs is feasible and safe. An acute increase in atrial tissue refractoriness is promising but further studies are required to see how this translates to longer term outcomes in symptomatic AF patients and in a percutaneous epicardial access setting.